Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas IV-A SDN Pakis 1 Surabaya - Widia Jala Setyaningrum; Bekti Wirawati; Nunuk Suliyastuti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to improve the learning outcomes of students in class IV-A in IPAS subjects, especially on the material of friction and muscle force, by using the Problem Based Learning (PBL) Learning Model at SDN Pakis 1 Surabaya. This research is a Classroom Action Research (PTK) conducted in two cycles, each of which consists of planning, implementation, observation, and reflection stages. The subjects of this study were 28 students of class IV-A. The instruments used include learning outcome tests to measure students' understanding of the material taught. The results showed a significant increase in student learning outcomes. At the pre-cycle stage, only 39% of students achieved mastery, while 61% of students were not yet complete. After the implementation of PBL, in cycle 1 student completeness increased to 71%, and in cycle 2 all students reached completeness with a percentage of 100%. PBL proved to be effective in improving students' understanding of the concepts of friction and muscle force through problem solving that is relevant to everyday life. Thus, the application of Problem Based Learning (PBL) can significantly improve student learning outcomes in IPAS subjects, especially in understanding abstract concepts such as force. This method is also effective in developing students' critical and collaborative thinking skills.